The Best Book on the Market : How to Stop Worrying and Love the Free Economy. - Butler, Eamonn (John Wiley & Sons, 2008)
The free market makes the world go around. Maybe it's time we all tried to understand it a little better. Luckily Eamonn Butler is the ideal teacher to get us all up to speed. Markets are everywhere. But how many of us understand how they work, and why? What does a 'free market' really mean? Do free markets actually exist? Should we have more or less of them? Most of all do we really need to know all this? Answer: Yes we do. MAKING ECONOMICS SIMPLE SO THAT EVEN POLITICIANS CAN UNDERSTAND IT. If any mention of free markets sends your mind screaming back to your musty old school economics text.